Noragami, stray god. 19 - Adachi, Toka (Kodansha Comics, 2017)
"Trial by pledge With Bishamon badly injured and Yato and Yukiné arrested by the Heavens, Tenjin has invoked their very last hope: a Trial by Pledge. If the plan works, Amaterasu will pardon all perceived wrongdoings, but the stakes are high. Three gods must pledge the lives of their most trusted shinki. The score is tied when Daikoku volunteers himself as a sacrifice..."--Amazon.